2009
DOI: 10.1111/j.1600-0501.2009.01799.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human bone morphogenetic protein‐2 on bone formation in the acute distraction osteogenesis of rat mandibles

Abstract: In conclusion, the study indicates that rhBMP-2 can enhance the bone formation at acute DO, which may potentially reduce the treatment period and complications related to the distraction procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
1
11
0
3
Order By: Relevance
“…Among the commonly used carriers, most of them are composed by collagen sponges (Tarnow et al, 2010), polylactic acid and polyglycolic (Aghaloo et al, 2010), membranes of different origins (Waris et al, 2010), hydroxyapatite (Xie et al, 2010), calcium sulfate and tricalcium phosphate (Sawyer et al, 2009). The carrier used in this study is the cubic phase of monoolein gel, which represents a material with bioadhesive, biodegradable, and biocompatible properties that has been used in the pharmaceutical industry because it represents an interesting releasing for drugs and medicines with different polarities and molecular weights for transdermal route (Shah et al, 2001), in addition, some previous studies have been conducted by the authors using the monoolein gel as a carrier for rhBMP-2 in different experimental animal models (Abdala et al, 2010;Balabanian et al, 2006;Issa et al, 2008Issa et al, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Among the commonly used carriers, most of them are composed by collagen sponges (Tarnow et al, 2010), polylactic acid and polyglycolic (Aghaloo et al, 2010), membranes of different origins (Waris et al, 2010), hydroxyapatite (Xie et al, 2010), calcium sulfate and tricalcium phosphate (Sawyer et al, 2009). The carrier used in this study is the cubic phase of monoolein gel, which represents a material with bioadhesive, biodegradable, and biocompatible properties that has been used in the pharmaceutical industry because it represents an interesting releasing for drugs and medicines with different polarities and molecular weights for transdermal route (Shah et al, 2001), in addition, some previous studies have been conducted by the authors using the monoolein gel as a carrier for rhBMP-2 in different experimental animal models (Abdala et al, 2010;Balabanian et al, 2006;Issa et al, 2008Issa et al, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies are establishing the safety and effectiveness of rapid distraction protocols and shorter consolidation phase by applying recombinant human bone morphogenetic protein to the bony regenerate, which is well known to hasten bone healing in fractures [41,42]. Such studies are clinically important since shortening the distraction and/or the consolidation phase may reduce the morbidity and cost associated with distraction osteogenesis.…”
Section: Future Direction Of Distraction Osteogenesismentioning
confidence: 98%
“…Excessive concentration of magnesium ions and pH value can cause the excess of BMP-2 secretion, activating osteoclasts, thereby causeing osteolytic phenomenon. BMP-2 is one of the important index to observe the new bone, which can cause local formation of new bones [13,14]. The study of BMP-2 on promoting bone formation showed that BMP-2 secreted exuberant, and the new bone formation was fast.…”
Section: Groupsmentioning
confidence: 99%